Implementation Of Organizational Culture And Work Discipline And Their Influence On Army Polytechnic Performance - Rachmat Setiawibawa (Pusat Riset dan Inovasi Nasional, 2022)
An organization is a place where people gather, and a system manages resources using methods, materials, environment, facilities and infrastructure efficiently and effectively, to achieve the same goal. In an organization, everyone works rationally, systematically, planned, controlled and guided in utilizing all resources. Strategic resources in an organization are people who play an important role in determining whether an organization is healthy or not. Therefore, planned and sustainable human resource development is an absolute necessity for organizational sustainability.